A method for preparing a high-humidity resistant poly 3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor

By using trisodium naphthalene-1,3,6-trisulfonate as a crosslinking agent and perfluoro compound to form a hydrophobic layer in a poly3,4-ethylenedioxythiophene sheet laminated aluminum electrolytic capacitor, the problem of increased leakage current of the capacitor and increased equivalent series resistance in humid environments is solved, and the stable performance of the capacitor in humid environments is achieved.

CN118366791BActive Publication Date: 2025-04-18FUJIAN GUOGUANG XINYE SCI TEC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410619942.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-04-18
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

When used in humid environments, the existing poly3,4-ethylenedioxythiophene chip laminated aluminum electrolytic capacitors have an increase in leakage current, an equivalent series resistance increases, and the changes are irreversible, which cannot meet the development trend of low internal resistance and high reliability.

Method used

By using trisodium naphthalene-1,3,6-trisulfonate with three sulfonate groups as crosslinking agent, combined with the hydrophobic properties of the perfluoro compound, electrochemical cyclic voltammetry oxidation polymerization reaction is carried out to form a crosslinked PEDOT molecular chain and a fluorine compound doping layer, reducing the voids between the molecular chains and avoiding contact of water molecules.

Benefits of technology

It realizes that when the aluminum electrolytic capacitor is used in a humid environment, the leakage current is low, the equivalent series resistance is small, and the capacitance is stable, and it has significant economic value and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of capacitor preparation, and in particular to a method for preparing a high-humidity resistant poly 3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor, comprising sequentially subjecting a formed foil to a primary chemical polymerization treatment, a secondary electrochemical polymerization treatment and a tertiary electrochemical polymerization treatment, and then coating with graphite, coating with silver paste, laminating and bonding, epoxy resin encapsulating and aging to obtain a polymer chip-type laminated aluminum electrolytic capacitor. The PEDOT chip-type laminated aluminum electrolytic capacitor prepared by the invention has the advantages of low leakage current, small equivalent series resistance, stable capacitance and the like when used for a long time in a humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of capacitor preparation, in particular to a method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene sheet-type laminated aluminum electrolytic capacitor. Background Art

[0002] At present, poly (3,4-ethylenedioxythiophene) (PEDOT) chip-type multilayer aluminum electrolytic capacitors are widely used in consumer electronics, computers, information communications and automotive electronics.

[0003] However, PEDOT is a linear polymer molecular chain. During the polymerization process, especially during the chemical oxidation polymerization process, the irregular arrangement of the PEDOT molecular chains will lead to large gaps between the molecular chains. In a humid environment, water molecules will contact the dielectric Al2O3 through the gaps. Under the action of the electric field, water molecules will corrode the dielectric Al2O3, causing the dielectric to be broken down and the leakage current of the aluminum electrolytic capacitor to increase; at the same time, under the action of the electric field, water molecules will seriously damage the silver layer on the surface of the negative electrode of the capacitor, causing the conductivity of the silver layer to decrease due to oxidation, increasing the equivalent series resistance of the capacitor, and this change is irreversible. Therefore, PEDOT chip-type laminated aluminum electrolytic capacitors used in humid environments cannot meet the development trend of low internal resistance and high reliability. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor. The prepared aluminum electrolytic capacitor has the advantages of low leakage current, small equivalent series resistance, stable capacitance, etc. when used for a long time in a humid environment, and has significant economic value and social benefits.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor comprises the following steps:

[0007] S1. First, 1-2 g of 3,4-ethylenedioxythiophene, 4-6 g of naphthalene-1,3,6-trisodium trisulfonate and 0.1-0.5 g of carboxymethyl cellulose are added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 20-60 min. The pH value of the solution is adjusted to 2-4 by p-toluenesulfonic acid to obtain a reducing solution. Then, 4-10 g of potassium permanganate is added to 100 mL of deionized water, and magnetically stirred at room temperature for 10-20 min to obtain an oxidizing solution. Finally, the formed foil is immersed in the oxidizing solution and the reducing solution in turn, and is immersed in deionized water and dried to obtain a chemically polymerized foil.

[0008] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the reducing solution prepared in step S1 as the electrolyte, after the electrochemical cyclic voltammetry oxidative polymerization reaction, the working electrode is taken out, rinsed with deionized water and dried to prepare the secondary electrochemical polymerization treated foil;

[0009] S3, first add 0.005-0.02 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, magnetically stir at room temperature for 10-30 min, then add 2-4 g of 3-fluorothiophene and 2-8 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue magnetic stirring for 30-60 min, adjust the pH value of the solution to 2-4 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution;

[0010] S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in step S3 as the electrolyte, after the electrochemical cyclic voltammetric oxidative polymerization reaction, the working electrode is taken out, rinsed with deionized water and dried to prepare the tertiary electrochemical polymerization-treated foil;

[0011] S5. The foil is subjected to three electrochemical polymerization treatments, and then is coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin, and aged to obtain a high-humidity resistant 3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0012] Preferably, during the one-time chemical polymerization treatment in step S1, the formed foil is first immersed in the oxidizing solution for 5 s, taken out, and dried at 80°C for 5 min, then immersed in the reducing solution for 10 s, taken out, and dried at 80°C for 5 min, and then alternately immersed in the oxidizing solution and the reducing solution, and the number of immersion cycles is 3 to 5 times.

[0013] Preferably, the silver paste in step S5 is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether modified polydimethylsiloxane at room temperature.

[0014] Preferably, the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 10 to 40 g of silver powder to 500 to 1000 mL of toluene, ultrasonicating at room temperature for 2 to 4 h, then adding 2 to 20 g of perfluorodecyltrimethoxysilane, magnetically stirring at 120 to 140 ° C for 4 to 8 h, filtering, washing and drying.

[0015] Preferably, the voltage scanning range of the electrochemical cyclic voltammetry oxidative polymerization reaction in step S2 is 0 V to 1.5 V, the scanning rate is 10 to 100 mV / s, and the cyclic scanning is 10 to 40 cycles.

[0016] Preferably, the voltage scanning range of the electrochemical cyclic voltammetry oxidative polymerization reaction in step S5 is 0 V to 1.5 V, the scanning rate is 10 to 100 mV / s, and the cycle scan is 5 to 20 cycles.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention uses trisodium naphthalene-1,3,6-trisulfonate having three sulfonate groups as a crosslinking agent, and the PEDOT molecular chains are crosslinked through the interaction between the sulfonate ions and the positively charged PEDOT molecular chains, thereby reducing the gaps between the PEDOT molecular chains; and the present invention uses sodium perfluorodecene-p-oxybenzenesulfonate as a dispersant, 3-fluorothiophene as a monomer, sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate as a dopant, and 4-fluorobenzenesulfonic acid as a pH regulator, and coats a layer of 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid-doped poly-3-fluorothiophene on the outside of PEDOT through an electrochemical cyclic voltammetric oxidative polymerization reaction. Due to the hydrophobic property of the fluorine element, the 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid-doped poly-3-fluorothiophene coating layer can prevent water molecules from contacting with the dielectric Al2O3, thereby effectively preventing the increase of leakage current of the PEDOT chip-type laminated aluminum electrolytic capacitor when used for a long time in a humid environment;

[0019] 2. The present invention adopts a silver paste designed and prepared independently as the negative electrode of the capacitor, wherein perfluorodecyltrimethoxysilane is grafted on the surface of the silver powder. Since the perfluoro compound on the surface of the silver powder has a strong hydrophobic effect, it can effectively prevent water molecules from contacting the silver powder. Therefore, the silver layer on the surface of the negative electrode of the capacitor prepared by the present invention is not easily damaged by water molecules. When used for a long time in a humid environment, the equivalent series resistance of the capacitor will not increase significantly.

[0020] 3. Because trisodium naphthalene-1,3,6-trisulfonate can reduce the gaps between PEDOT molecular chains, the hydrophobic effect of fluorine-containing compounds can effectively prevent water molecules from contacting the dielectric Al2O3 or the silver layer on the negative electrode surface. Therefore, the PEDOT chip-type laminated aluminum electrolytic capacitor prepared by the present invention has the advantages of low leakage current, small equivalent series resistance, stable capacitance, etc. when used for a long time in a humid environment, and has significant economic value and social benefits. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1:

[0023] S1. First, 1.5 g of 3,4-ethylenedioxythiophene, 5 g of naphthalene-1,3,6-trisulfonic acid trisodium and 0.3 g of carboxymethyl cellulose were added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 40 min. The pH value of the solution was adjusted to 3 by p-toluenesulfonic acid to obtain a reducing solution. Then, 7 g of potassium permanganate was added to 100 mL of deionized water, and magnetically stirred at room temperature for 15 min to obtain an oxidizing solution. Finally, the chemical foil was immersed in the oxidizing solution and the reducing solution in turn, and was immersed in deionized water and dried to obtain a chemical polymerization-treated chemical foil; wherein, the chemical foil was first immersed in the oxidizing solution for 5 s, taken out, dried at 80°C for 5 min, and then immersed in the reducing solution for 10 s. After being taken out, dried at 80°C for 5 min, and then immersed in the reducing solution for 4 times.

[0024] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the reducing solution prepared in step S1 as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidative polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 50 mV / s, and a cycle scan of 25 times, taking out the working electrode, rinsing with deionized water and drying, to obtain a secondary electrochemical polymerization treated foil;

[0025] S3, first add 0.01 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, stir magnetically at room temperature for 20 min, then add 3 g of 3-fluorothiophene and 5 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue to stir magnetically for 45 min, adjust the pH value of the solution to 3 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution;

[0026] S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in step S3 as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidative polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 50 mV / s, and a cyclic scan of 10 circles, taking out the working electrode, rinsing with deionized water and drying it, to obtain a tertiary electrochemical polymerization-treated foil;

[0027] S5. The foil is subjected to three electrochemical polymerization treatments, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin, and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0028] In step S5, the silver paste is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane-treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether-modified polydimethylsiloxane at room temperature, wherein the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 25 g of silver powder to 750 mL of toluene, ultrasonicating at room temperature for 3 h, then adding 10 g of perfluorodecyltrimethoxysilane, magnetically stirring at 130 °C for 6 h, filtering, washing and drying.

[0029] Embodiment 2:

[0030] S1. First, 1 g of 3,4-ethylenedioxythiophene, 4 g of trisodium naphthalene-1,3,6-trisulfonate and 0.1 g of carboxymethyl cellulose were added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 20 min. The pH value of the solution was adjusted to 2 by p-toluenesulfonic acid to obtain a reducing solution. Then, 4 g of potassium permanganate was added to 100 mL of deionized water, and magnetically stirred at room temperature for 10 min to obtain an oxidizing solution. Finally, the formed foil was immersed in the oxidizing solution and the reducing solution in turn, and was immersed in deionized water and dried to obtain a chemical polymerization-treated formed foil, wherein the formed foil was first immersed in the oxidizing solution for 5 s, taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 10 s. After being taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 5 times.

[0031] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the reducing solution prepared in step S1 as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidative polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 10 mV / s, and a cyclic scan of 10 circles, taking out the working electrode, rinsing with deionized water and drying it, to obtain a secondary electrochemical polymerization treated foil;

[0032] S3, first add 0.005 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, magnetically stir at room temperature for 10 min, then add 2 g of 3-fluorothiophene and 2 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue magnetic stirring for 30 min, adjust the pH value of the solution to 2 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution;

[0033] S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in step (3) as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidative polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 10 mV / s, and a cycle scan of 5 times, taking out the working electrode, rinsing it with deionized water and drying it, to obtain a tertiary electrochemical polymerization-treated foil;

[0034] S5. The foil is subjected to three electrochemical polymerization treatments, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin, and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0035] The silver paste in S5 is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane-treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether-modified polydimethylsiloxane at room temperature, wherein the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 10 g of silver powder to 500 mL of toluene, ultrasonicating at room temperature for 2 h, then adding 2 g of perfluorodecyltrimethoxysilane, magnetically stirring at 120 °C for 8 h, filtering, washing and drying.

[0036] Embodiment 3:

[0037] (1) First, 2 g of 3,4-ethylenedioxythiophene, 6 g of trisodium naphthalene-1,3,6-trisulfonate and 0.5 g of carboxymethyl cellulose were added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 60 min. The pH value of the solution was adjusted to 4 with p-toluenesulfonic acid to obtain a reducing solution. Then, 10 g of potassium permanganate was added to 100 mL of deionized water, and magnetically stirred at room temperature for 20 min to obtain an oxidizing solution. Finally, the formed foil was immersed in the oxidizing solution and the reducing solution in turn, and was immersed in deionized water and dried to obtain a chemical polymerization treated formed foil, wherein the formed foil was first immersed in the oxidizing solution for 5 s, taken out, dried at 80°C for 5 min, and then immersed in the reducing solution for 10 s. After being taken out, dried at 80°C for 5 min, and then alternately immersed in the oxidizing solution and the reducing solution. The number of immersion cycles was 3 times.

[0038] (2) using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the reducing solution prepared in step (1) as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidation polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 100 mV / s, and a cycle scan of 40 times, taking out the working electrode, rinsing it with deionized water and drying it, to obtain a secondary electrochemical polymerization treated foil;

[0039] (3) First, add 0.02 g of sodium perfluorodecene-4-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, stir magnetically at room temperature for 30 min, then add 4 g of 3-fluorothiophene and 8 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue to stir magnetically for 60 min, and adjust the pH value of the solution to 4 with 4-fluorobenzenesulfonic acid to obtain a fluorine-containing mixed solution;

[0040] (4) using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in step (3) as the electrolyte, to carry out an electrochemical cyclic voltammetric oxidative polymerization reaction, with a voltage scan range of 0 V to 1.5 V, a scan rate of 100 mV / s, and a cycle scan of 20 times, taking out the working electrode, rinsing it with deionized water and drying it, to obtain a tertiary electrochemical polymerization-treated foil;

[0041] (5) The foil is subjected to three electrochemical polymerization treatments, and then is coated with graphite, coated with silver paste, laminated, bonded, encapsulated with epoxy resin, and aged to obtain the high-humidity resistant poly(3,4-ethylenedioxythiophene) chip-type laminated aluminum electrolytic capacitor.

[0042] The silver paste is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane-treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether-modified polydimethylsiloxane at room temperature, wherein the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 40 g of silver powder to 1000 mL of toluene, ultrasonicating at room temperature for 4 h, then adding 20 g of perfluorodecyltrimethoxysilane, magnetically stirring at 140 °C for 4 h, filtering, washing and drying.

[0043] Comparative Example 1:

[0044] S1. First, 1.5 g of 3,4-ethylenedioxythiophene and 0.3 g of carboxymethyl cellulose were added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 40 min. The pH value of the solution was adjusted to 3 by p-toluenesulfonic acid to obtain a reducing solution. Then, 7 g of potassium permanganate was added to 100 mL of deionized water, and magnetically stirred at room temperature for 15 min to obtain an oxidizing solution. Finally, the formed foil was immersed in the oxidizing solution and the reducing solution in turn, and was immersed in deionized water and dried to obtain a chemically polymerized foil. The formed foil was first immersed in the oxidizing solution for 5 s, taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 10 s. After being taken out, dried at 80 ° C for 5 min, and then immersed in the oxidizing solution and the reducing solution alternately. The number of immersion cycles was 4 times.

[0045] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the reducing solution prepared in S1 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 25 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the secondary electrochemical polymerization treated foil;

[0046] S3, first add 0.01 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, stir magnetically at room temperature for 20 min, then add 3 g of 3-fluorothiophene and 5 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue to stir magnetically for 45 min, adjust the pH value of the solution to 3 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution;

[0047] S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in S3 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 10 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the tertiary electrochemical polymerization-treated foil;

[0048] S5. The foil is subjected to three electrochemical polymerization treatments, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin, and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0049] In addition, the silver paste in S5 is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane-treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether-modified polydimethylsiloxane at room temperature, wherein the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 25 g of silver powder to 750 mL of toluene, ultrasonicating at room temperature for 3 h, then adding 10 g of perfluorodecyltrimethoxysilane, magnetically stirring at 130 °C for 6 h, filtering, washing and drying.

[0050] Comparative Example 2

[0051] S1, first add 1.5 g 3,4-ethylenedioxythiophene, 5 g naphthalene-1,3,6-trisulfonic acid trisodium and 0.3 g carboxymethyl cellulose to 100 mL ethanol solution with a concentration of 50 wt%, stir magnetically at room temperature for 40 min, adjust the pH value of the solution to 3 with p-toluenesulfonic acid to obtain a reducing solution, then add 7 g potassium permanganate to 100 mL deionized water, stir magnetically at room temperature for 15 min to obtain an oxidizing solution, and finally immerse the formed foil in the oxidizing solution and the reducing solution in turn, soak and dry the foil in deionized water to obtain a chemical polymerization-treated formed foil, wherein the formed foil is first immersed in the oxidizing solution for 5 s, taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 10 s, taken out, dried at 80 ° C for 5 min, and then alternately immersed in the oxidizing solution and the reducing solution, and the number of immersion cycles is 4 times;

[0052] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the reducing solution prepared in S1 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 25 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the secondary electrochemical polymerization treated foil;

[0053] S3, the foil is subjected to secondary electrochemical polymerization treatment, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0054] In addition, the silver paste is prepared by fully stirring 85 wt% of perfluorodecyltrimethoxysilane-treated silver powder, 3 wt% of glass powder, 6.8 wt% of epoxy resin EP1001, 3 wt% of butyl acetate, 2 wt% of hydrogenated castor oil and 0.2 wt% of polyether-modified polydimethylsiloxane at room temperature, wherein the perfluorodecyltrimethoxysilane-treated silver powder is prepared by first adding 25 g of silver powder to 750 mL of toluene, ultrasonicating at room temperature for 3 h, then adding 10 g of perfluorodecyltrimethoxysilane, magnetically stirring at 130 °C for 6 h, filtering, washing and drying.

[0055] Comparative Example 3

[0056] S1, first add 1.5 g 3,4-ethylenedioxythiophene, 5 g naphthalene-1,3,6-trisulfonic acid trisodium and 0.3 g carboxymethyl cellulose to 100 mL ethanol solution with a concentration of 50 wt%, stir magnetically at room temperature for 40 min, adjust the pH value of the solution to 3 with p-toluenesulfonic acid to obtain a reducing solution, then add 7 g potassium permanganate to 100 mL deionized water, stir magnetically at room temperature for 15 min to obtain an oxidizing solution, and finally immerse the formed foil in the oxidizing solution and the reducing solution in turn, soak and dry the foil in deionized water to obtain a chemical polymerization-treated formed foil, wherein the formed foil is first immersed in the oxidizing solution for 5 s, taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 10 s, taken out, dried at 80 ° C for 5 min, and then alternately immersed in the oxidizing solution and the reducing solution, and the number of immersion cycles is 4 times;

[0057] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the reducing solution prepared in S1 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 25 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the secondary electrochemical polymerization treated foil;

[0058] S3, first add 0.01 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, stir magnetically at room temperature for 20 min, then add 3 g of 3-fluorothiophene and 5 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue to stir magnetically for 45 min, adjust the pH value of the solution to 3 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution;

[0059] S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in S3 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 10 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the tertiary electrochemical polymerization-treated foil;

[0060] S5. The foil is subjected to three electrochemical polymerization treatments, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin, and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0061] The silver paste is prepared by fully stirring 85 wt% silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether modified polydimethylsiloxane at room temperature.

[0062] Comparative Example 4

[0063] S1. First, 1.5 g of 3,4-ethylenedioxythiophene and 0.3 g of carboxymethyl cellulose were added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 40 min. The pH value of the solution was adjusted to 3 by p-toluenesulfonic acid to obtain a reducing solution. Then, 7 g of potassium permanganate was added to 100 mL of deionized water, and magnetically stirred at room temperature for 15 min to obtain an oxidizing solution. Finally, the formed foil was immersed in the oxidizing solution and the reducing solution in turn, and was immersed in deionized water and dried to obtain a chemically polymerized foil. The formed foil was first immersed in the oxidizing solution for 5 s, taken out, dried at 80 ° C for 5 min, and then immersed in the reducing solution for 10 s. After being taken out, dried at 80 ° C for 5 min, and then immersed in the oxidizing solution and the reducing solution alternately. The number of immersion cycles was 4 times.

[0064] S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, platinum wire as the counter electrode, saturated calomel electrode as the reference electrode, and the reducing solution prepared in S1 as the electrolyte, an electrochemical cyclic voltammetric oxidative polymerization reaction was carried out, the voltage scanning range was 0 V~1.5 V, the scanning rate was 50 mV / s, and the cycle scanning was 25 circles. The working electrode was taken out, rinsed with deionized water and dried to obtain the secondary electrochemical polymerization treated foil;

[0065] S3, the foil is subjected to secondary electrochemical polymerization treatment, and then coated with graphite, coated with silver paste, laminated and bonded, encapsulated with epoxy resin and aged to obtain the high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor.

[0066] The silver paste is prepared by fully stirring 85 wt% silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether modified polydimethylsiloxane at room temperature.

[0067] The capacitors prepared in three groups of embodiments and four groups of comparative examples were tested for capacitance (C), leakage current (Lc) and equivalent series resistance (ESR) in a high humidity environment according to GB / T 6346.25-2018. The test conditions were an ambient temperature of 60±2°C, an ambient relative humidity of 92±3%RH, and a duration of 480 h. The test results are shown in the following table, where the values ​​in brackets are percentage changes in performance.

[0068]

[0069] Conclusion: From the test results of the three groups of embodiments and the four groups of comparative examples, it can be seen that under the same test conditions, the change rates of the capacitance, leakage current and equivalent series resistance of the capacitors obtained in the three groups of embodiments are all smaller than the change rates of the capacitance, leakage current and equivalent series resistance of the capacitors obtained in the four groups of comparative examples. This indicates that the poly (3,4-ethylenedioxythiophene) sheet-type laminated aluminum electrolytic capacitor with low leakage current, small equivalent series resistance and stable capacitance when used for a long time in a humid environment can be obtained by first subjecting the formed foil to a primary chemical polymerization treatment, a secondary electrochemical polymerization treatment and a tertiary electrochemical polymerization treatment in sequence, and then coating with graphite, coating with silver paste, laminating and bonding, epoxy resin encapsulating and aging.

[0070] The above description shows and describes the preferred embodiments of the present invention. As mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor, characterized in that: The following steps are involved: S1. First, 1-2 g of 3,4-ethylenedioxythiophene, 4-6 g of naphthalene-1,3,6-trisodium trisulfonate and 0.1-0.5 g of carboxymethyl cellulose are added to 100 mL of 50 wt% ethanol solution, and magnetically stirred at room temperature for 20-60 min. The pH value of the solution is adjusted to 2-4 by p-toluenesulfonic acid to obtain a reducing solution. Then, 4-10 g of potassium permanganate is added to 100 mL of deionized water, and magnetically stirred at room temperature for 10-20 min to obtain an oxidizing solution. Finally, the formed foil is immersed in the oxidizing solution and the reducing solution in turn, and is immersed in deionized water and dried to obtain a chemically polymerized foil. S2, using a three-electrode system, with the primary chemical polymerization treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the reducing solution prepared in step S1 as the electrolyte, after the electrochemical cyclic voltammetry oxidative polymerization reaction, the working electrode is taken out, rinsed with deionized water and dried to prepare the secondary electrochemical polymerization treated foil; S3, first add 0.005-0.02 g of sodium perfluorodecene-p-oxybenzenesulfonate to 100 mL of 50 wt% ethanol solution, magnetically stir at room temperature for 10-30 min, then add 2-4 g of 3-fluorothiophene and 2-8 g of sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate, continue magnetic stirring for 30-60 min, adjust the pH value of the solution to 2-4 with 4-fluorobenzenesulfonic acid, and prepare a fluorine-containing mixed solution; S4, using a three-electrode system, with the secondary electrochemical polymerization-treated foil as the working electrode, the platinum wire as the counter electrode, the saturated calomel electrode as the reference electrode, and the fluorine-containing mixed solution prepared in step S3 as the electrolyte, after the electrochemical cyclic voltammetric oxidative polymerization reaction, the working electrode is taken out, rinsed with deionized water and dried to prepare the tertiary electrochemical polymerization-treated foil; S5, the foil is subjected to three electrochemical polymerization treatments, and then coated with graphite, coated with silver paste, laminated, bonded, encapsulated with epoxy resin, and aged to obtain a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor; The silver paste in the silver paste coating process is prepared by fully stirring 85 wt% perfluorodecyltrimethoxysilane treated silver powder, 3 wt% glass powder, 6.8 wt% epoxy resin EP1001, 3 wt% butyl acetate, 2 wt% hydrogenated castor oil and 0.2 wt% polyether modified polydimethylsiloxane at room temperature.

2. The method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor according to claim 1, characterized in that: During the one-time chemical polymerization treatment in step S1, the formed foil is first immersed in the oxidizing solution for 5 s, taken out, and dried at 80°C for 5 min, then immersed in the reducing solution for 10 s, taken out, and dried at 80°C for 5 min, and then alternately immersed in the oxidizing solution and the reducing solution, and the number of immersion cycles is 3 to 5 times.

3. The method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The perfluorodecyltrimethoxysilane treated silver powder is prepared by first adding 10-40 g of silver powder into 500-1000 mL of toluene, ultrasonicating at room temperature for 2-4 h, then adding 2-20 g of perfluorodecyltrimethoxysilane, magnetically stirring at 120-140 °C for 4-8 h, filtering, washing and drying.

4. The method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The voltage scanning range of the electrochemical cyclic voltammetry oxidative polymerization reaction in step S2 is 0 V to 1.5 V, the scanning rate is 10 to 100 mV / s, and the cyclic scanning is 10 to 40 cycles.

5. The method for preparing a high-humidity resistant poly-3,4-ethylenedioxythiophene chip-type laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The voltage scanning range of the electrochemical cyclic voltammetry oxidative polymerization reaction in step S5 is 0 V to 1.5 V, the scanning rate is 10 to 100 mV / s, and the cyclic scanning is 5 to 20 circles.

Citation Information

Patent Citations

  • Preparation method of lamination sheet type polymer solid aluminum electrolytic capacitor

    CN105374563A

  • Preparation and application of artificial solid electrolyte buffer layer

    CN116411292A